Loneliness mediates the association between sleep deficiency and fighting in school-aged adolescents: a 2-year longitudinal study - Wei Wei; Lu Pan; Si-Xuan Li; Si-Jia Wang; Qing-Hai Gong; Xin Xiao (Scientific Reports)
Abstract Sleep deficiency is becoming increasingly common among adolescents and may lead to aggressive behaviour. This study investigated the association between sleep deficiency and fighting among 1946 school-aged adolescents (mean age: 12.2 ± 0.47 years) in Ningbo city through a two-year longitudinal study and explored the mediating roles of loneliness, sadness, and nervousness. A total of 552 (28.3%) reported sleep deficiency at baseline. During the follow-up period, 347 (17.8%) adolescents engaged in fighting. Sleep deficiency was significantly associated with an increased likelihood of fighting (OR: 1.91, 95% CI: 1.45–2.52) after adjusting for confounders. Compared with boys, girls with sleep deficiency presented a greater risk of fighting (OR: 2.61, 95% CI: 1.44–4.73 for girls; OR: 1.74, 95% CI: 1.27–2.39 for boys). This association persists among adolescents with unhealthy lifestyles. Loneliness partially mediated this relationship (indirect effect β = 0.013, P < 0.05, effect ratio = 12.26%), whereas sadness and nervousness had no significant mediating effect. Studies have shown that sleep deficiency independently predicts adolescent fighting behaviour, with loneliness playing a key mediating role. Interventions that improve sleep hygiene, reduce loneliness, and address lifestyle likelihood factors may help reduce violent behaviour in adolescents.